Analisis Daya Dukung Tanah Pondasi Dalam Berdasarkan Data Lapangan Di Desa Baringin Kota Palangka Raya - Amanda Rachmad Pratama; Rida Respati; Norseta Ajie Saputra (Media Ilmiah Teknik Sipil, 2020)
Soil bearing capacity is the ability of the soil to support the foundation load acting on it. To produce an accurate bearing capacity, it is necessary to know the properties and characteristics of the soil. For this reason, a comparison of the carrying capacity of the soil is carried out based on the calculation of CPT / Sondir and SPT to be able to plan a safe and economical pile foundation. The purpose of this study was to determine the amount of soil bearing capacity of the deep foundation in the environment around the Ataqwa Mosque, Baringin Village, Palangkaraya City based on field tests, and based on laboratory tests, and to determine the value of the comparison between the Mayerhof Method and the Schmertmann-Nottingham Method. Based on the Sondir value, it is continued with the calculation of the carrying capacity of the soil, then the calculation results are analyzed and concluded. From the calculation of the value of the carrying capacity of the foundation pile implementation of point 1 (one), the highest value of 400 mm diameter piles in the Meyerhoff method is 75,319 kg, while the lowest bearing capacity value is also at 400 mm piles of 10,676 kg. For point 2 (two), the highest value is obtained at 400 mm diameter piles in the Shmertmann-Nottingham method of 65,853 kg, while the lowest bearing capacity value is also at 400 mm piles of 10,676 kg